An optical fiber Fabry–Pérot micro-pressure sensor based on beam-membrane structure. (23rd October 2018) - Tian, Bian; Zhan, Feng; Han, Feng; Li, Kaikai; Zhao, Na; Yang, Ning; Jiang, Zhuangde
Abstract: In this paper, an optical fiber Fabry–Pérot (FP) sensor for micro-pressure measurement is proposed. The FP interferometric cavity is composed of an end face of the incident optical fiber and a sensitive silicon diaphragm. The sensitive silicon diaphragm creatively utilizes a beam-membrane structure which is fabricated by micro-electro-mechanical system manufacturing technology. The finite element method simulation results show that the beam-membrane structure can achieve higher sensitivity and better linearity. The sensor performance test platform is built by a ASE-wide spectrum light source, optical spectrum analyzer, micro-pressure gas source and so on. The phase demodulation method is employed to demodulate the cavity length signal from the spectrum. The measure range of the sensor is 0–10 KPa, and the experimental sensitivity of the cavity length can reach to 242 nm KPa −1 .